(untitled) (The Journal of Knowledge and Innovation, 2024)
This study was conducted in Cooch Behar District, West Bengal, India, to see how different formulated feeds affect the growth of Indian major carps — Catla catla, Labeo rohita, and Cirrhinus mrigala. The experiment was done over four years (2008–2012) in farmers’ ponds using four types of feed made from fishmeal, soybean meal, silkworm pupae, and mustard oilcake. Treated ponds received artificial feed, while control ponds did not. The results showed that carps in treated ponds grew faster and became heavier than those in control ponds. Among the feeds, silkworm pupae-based feed (Feed C) gave the best growth results and lowest feed conversion ratio (FCR), meaning fish grew more with less feed. Mustard oilcake-based feed (Feed D) showed the least growth. The study proves that using properly formulated feed, especially with good protein and fat sources like silkworm pupae, can greatly improve fish farming outcomes.